2017
DOI: 10.1080/15476286.2016.1269994
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of miR-221 and miR-222 reveals common and specific targets for paralogous miRNAs

Abstract: MicroRNAs (miRNAs) regulate the expression of mRNA through sequence-specific binding of the 3 0 untranslated region (UTR). The seed sequence of miRNAs is the key determinant for target site recognition. Paralogous miRNAs, which share the same seed sequences but differ in their 3 0 regions, are known to regulate largely overlapping groups of mRNAs. However, no study has analyzed functional differences between paralogous miRNAs with proper experimental methods. In this study, we compared the targets of paralogou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…The expression of ADAM22 detected by qRT-PCR in macrophages after ADAM22 siRNA transfection. [39][40][41] This finding highly agrees with our results in this study, because cancer cells generally escape programmed cell death, causing accumulated DNA damage and abolished apoptosis. C, Quantification of the oil red intensity in (B), ***P represents a significant difference compared with the ox-LDL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The expression of ADAM22 detected by qRT-PCR in macrophages after ADAM22 siRNA transfection. [39][40][41] This finding highly agrees with our results in this study, because cancer cells generally escape programmed cell death, causing accumulated DNA damage and abolished apoptosis. C, Quantification of the oil red intensity in (B), ***P represents a significant difference compared with the ox-LDL.…”
Section: Discussionsupporting
confidence: 92%
“…C, Quantification of the oil red intensity in (B), ***P represents a significant difference compared with the ox-LDL. 21,[44][45][46][47] A recent study conducted by Jeong et al 40 has suggested common and exclusive targets for miR-221 and miR-222 using nuclease-mediated knockout cell line. *P < 0.05 vs the ox-LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that these two miRNAs have similar functions and expression patterns [ 29 , 30 ]. However, miRNAs with the same seed sequences do not always regulate the same target genes [ 31 ]. Further examination is needed to demonstrate the role of miR-221 in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A functional role for 3' pairing has also recently been corroborated in vitro in mammalian cells and in vivo in C. elegans (Broughton et al 2016;Jeong et al 2017;Zhang et al 2015). The collective implication of these studies is that the 3' region of a given miRNA may confer an important but as-yet-undefined role in determining the target spectrum (and thus function) of the miRNA.…”
Section: Introductionmentioning
confidence: 83%